2007
DOI: 10.1038/sj.bjp.0706943
|View full text |Cite
|
Sign up to set email alerts
|

The effects induced by the sulphonylurea glibenclamide on the neonatal rat spinal cord indicate a novel mechanism to control neuronal excitability and inhibitory neurotransmission

Abstract: Background and purpose: Using the neonatal rat spinal cord in vitro, we investigated the action of glibenclamide, a drug possessing dual pharmacological effects, namely block of K ATP channels and of the cystic fibrosis transmembrane conductance regulator (CFTR). Experimental approach: Intra-and extracellular recordings were performed on motoneurons and interneurons. RT-PCR and western immunoblotting were used to determine gene and protein expression. Key results: Glibenclamide (50 mM) facilitated mono-and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Glibenclamide produced motoneuron resistance increase and membrane hyperpolarization consistent with the inhibition of a background outward conductance that was comparatively similar at P1 and P8. Our previous investigation has shown changes in passive membrane motoneuron properties produced by glibenclamide to be readily accounted by inhibition of a CFTR-dependent background conductance (Ostroumov, 2007;Ostroumov et al, 2007). Assuming that this effect of glibenclamide is due to inhibition of CFTR which is already largely expressed at somatic level of motoneurons even at P1, we may suggest that there is a CFTR-modulated leak inward conductance that regulates the basic somatic properties.…”
Section: Glibenclamide Actions On Passive Membrane Properties Of Motomentioning
confidence: 90%
See 1 more Smart Citation
“…Glibenclamide produced motoneuron resistance increase and membrane hyperpolarization consistent with the inhibition of a background outward conductance that was comparatively similar at P1 and P8. Our previous investigation has shown changes in passive membrane motoneuron properties produced by glibenclamide to be readily accounted by inhibition of a CFTR-dependent background conductance (Ostroumov, 2007;Ostroumov et al, 2007). Assuming that this effect of glibenclamide is due to inhibition of CFTR which is already largely expressed at somatic level of motoneurons even at P1, we may suggest that there is a CFTR-modulated leak inward conductance that regulates the basic somatic properties.…”
Section: Glibenclamide Actions On Passive Membrane Properties Of Motomentioning
confidence: 90%
“…However, CFTR expression in nonepithelial cells like macrophages, lymphocytes, neutrophils, and smooth muscle cells has been reported (Fonknechten et al, 1992;Di et al, 2006;Painter et al, 2006;Vandebrouck et al, 2006). Although CFTR expression has been found in neurons of the central nervous system (Mulberg et al, 1994;Ostroumov et al, 2007;Guo et al, 2009), its role remains unclear.…”
mentioning
confidence: 94%
“…The motoneuron morphology is shown in Fig. 5a, while somatic R m was drastically decreased (166 cm 2 ) to simulate sharp electrode penetration with resultant fall of input resistance to 22 M as often observed (Ostroumov et al, 2007), while antidromic action potentials could still be successfully generated.…”
Section: Modelling Of Cftr Inhibitor Action On Motoneurons Input Resimentioning
confidence: 94%
“…Our recent study (Ostroumov et al, 2007) suggested the expression of cystic fibrosis transmembrane conductance regulator (CFTR) in neonatal rat spinal motoneurons. Application of CFTR antagonists like glibenclamide increased input resistance and spike overshoot.…”
Section: Modelling Of Cftr Inhibitor Action On Motoneurons Input Resimentioning
confidence: 99%
“…Even if these symptoms may result from a complex association of diabetes, autoimmunity and vitamin deficiency, a primary CFTR defect is also likely to be involved as shown by the recent report of peripheral nervous system defects observed in CFTR -/-pigs at birth (Reznikov et al 2013). Concerning CFTR protein function, recent works have studied CFTR activity in motor neurons of the spinal cord or brainstem nuclei in rats during neonatal development (Ostroumov et al 2007;Morales et al 2011) and have shown that CFTR contributes to the relatively depolarized equilibrium potential for synaptic inhibition, an important process to control hyperexcitability and seizure-predisposition in neonates (Ostroumov et al 2007). It has also been shown that CFTR plays a role in postsynaptic inhibition of motor neurons from the trigeminal motor nucleus during rapid-eye-movement (REM) sleep (Morales et al 2011).…”
Section: Discussionmentioning
confidence: 99%